Genetic component analysis for seed yield and component traits in Indian mustard (Brassica juncea L.) - Sneha Adhikari; Sanjana Pathak; Deepak Joshi; Usha Pant; AK Singh; Ram Bhajan (Journal of Oilseed Brassica, 2026)
Ten diverse Indian mustard genotypes/parents suitable for different sowing condition were mated in half diallele designto know the nature of gene action for inheritance of seed yield and its components traits. The results showed thepresence of sufficient amount of variability among the experimental material used for the study. The estimates of σ2S werefound to be higher than the σ2g for all characters under study that indicated preponderance of non-additive gene actionfor inheritance of characters thereby suggesting heterosis breeding as the best method of improvement. The geneticadvance (GA) ranged from 0.043 for siliqua density on main raceme to 4.929 for plant height. Higher heritability accompaniedby higher genetic advance under selection was found in case of glucosinolate content, seed yield/ plant, number ofsiliquae on main raceme, number of secondary branches/plant and days to maturity. For all the traits under study thevalue of predictability ratio was lower than unity. It represented the involvement of non-fixable type of variance. Degreeof dominance ranged from 3.38 to 1.55. Therefore based on the results it can be concluded that all the characters understudy were governed by non-additive gene action so heterosis breeding can be utilized for further improvement